VOICE CHAT WEB APP USING WEBRTC - Tiwari, Avdhesh; Gupta, Harshit; Mittal, Sangam; Rawat, Mayank (IJRDO -Journal of Computer Science Engineering, 2022)
Technology improvements have made it possible to communicate more effectively. New technologies have improved existing communication routes. Some real-time communication systems include limitations, such as the need for additional software plugins and downloads to enable real-time communication, as well as security problems. Web Real-time Communication (WebRTC) is a technology that may be able to assist in the resolution of these issues. Thanks to advancements in internet technology, people may now easily access the internet. With the help of technological improvements, the internet is providing an increasing variety of services, all of which can be virtualized. People’s internet communication has become ingrained in their daily lives. People used to communicate with one another by exchanging voice chat messages via the internet.In order to achieve scalability, the platform also makes use of cloud computing. The iterative platform architectural design is revealed, as well as some preliminary scalability analysis results.